Molecular diagnosis of echovirus 30 as the etiological agent in an outbreak of aseptic meningitis in Panama: May – June 2008 - Alexander A Martinez; Juan Castillo; Mirla C Sanchez; Yamitzel Zaldivar; Yaxelis Mendoza; Maribel Tribaldos; Pablo Acosta; Rebecca E Smith; Juan Miguel Pascale (Journal of Infection in Developing Countries)
Introduction: Aseptic meningitis outbreaks are commonly caused by viral pathogens with enterovirus a common etiological agent. Between May and June of 2008, an outbreak of 173 cases of aseptic meningitis occurred in the Chiriqui Province of Panama. Molecular techniques were used to identify the etiological agent.